The Urgency of the Criminal Provision Regulationss in Cooperatives Law at Indonesia - Arie Kartika (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The essence of cooperatives is to remain themselves as cooperatives and not deviate into other forms, the moral values that underlie them must be realities of life in the activities and behavior of cooperative people. Evil develops along with the development and change of human life. The types are even more diverse with varied modus operandi, all following the development of increasingly modern humans, one of which is the crime of corruption and money laundering. Likewise, crime in the economy follows the sophistication of the development of the world economy. Crimes in the economic field are very likely to occur and affect the cooperative business entity. Based on this, the main problems of criminal acts cannot be avoided in the regulations of cooperative business activities. Determination of a law as a criminal acts means the law is prohibited, and should be given a criminal sanction. Crime in the Cooperative is identified as a problem that needs to be sought as an alternative sanction as a last resort in terms of law enforcement. The development of economic life requires a normative framework to maintain social order. Then it is necessary to administer the law with real legal objectives to facilitate the economic life of the Indonesian state.